THE POLARIZATION OF ORIENTATION AMONG STAKEHOLDERS ON INTERPRETATION SUBJECTS AT GUNUNG GEDE PANGRANGO NATIONAL PARK - Helianthi Dewi; Ricky Avenzora; Dudung Darusman; Cecep Kusmana (Secretariat of Agency for Standardization of Environment and Forestry Instruments, 2022)
Interpretation subject is a novel approach to observing resources in the interpretation program. Interpretation programs refer to the efforts to develop an individual's ability to deeply interpret the value of nature for humans through meaningful and pleasant experiences, impressions, and feelings to achieve management goals. The viewpoint of interpretation subject considers the intrinsic value of each resource. These polarization studies provide valuable information on critical issues concerning stakeholder perception and their implications for managing interpretations. The purpose of this study is to analyze and evaluate the characteristics of the interpretation subject that stakeholders thought were crucial in Gunung Gede Pangrango National Park management. The survey was done by distributing questionnaires to related stakeholders (tourists, communities, and area managers/tour operators) and evaluated by cluster analysis, Kruskal-Wallis, and Mann-Whitney test. Although the stakeholder considered flora, language, and abiotic components essential in interpretation, tourists' perception tended to focus on abiotic components and the built natural environment. The research showed that abiotic and cultural component-based-ecotourism-programs shall be developed to ensure sustainable management, increase community participation, and introduce the biological wealth in the national park area